2009
DOI: 10.1596/1813-9450-4822
|View full text |Cite
|
Sign up to set email alerts
|

Leveling The Intra-Household Playing Field: Compensation And Specialization In Child Labor Allocation

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…A shift from wage employment to entrepreneurial activities occurred in Mexico (Gertler et al, 2006). Child labor declined in Mexico, Nicaragua, and the Philippines as the CCT allowed children to stay in school rather than work in farms (Del Carpio & Macours, 2009; DSWD, 2014; Skoufias & Parker, 2001). 3…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…A shift from wage employment to entrepreneurial activities occurred in Mexico (Gertler et al, 2006). Child labor declined in Mexico, Nicaragua, and the Philippines as the CCT allowed children to stay in school rather than work in farms (Del Carpio & Macours, 2009; DSWD, 2014; Skoufias & Parker, 2001). 3…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Most of the out-of-school children identified as eligible to receive EpC were 5-7 years old and had never been to school, indicating that EpC was not successful at recruiting older out-of-school children who had either dropped out or had never enrolled. Prior research in Nicaragua indicates that labor competes with children's participation in school (e.g., Del Carpio & Macours, 2009). When the EpC model was first tested in Nicaragua, one of the recommendations was to add components such as income generation and technical training for families of working children to compensate for income lost when children leave work to return to school (Macro International Inc. 2009).…”
Section: Recommendationsmentioning
confidence: 99%
“…Our paper contributes to a large literature on the role of cash transfers in alleviating poverty. There is strong evidence that a regular flow of cash transfers can cushion the negative income effects of shocks and thus limit the use of costly coping mechanisms, albeit partially (Janvry et al, 2006;Del Carpio and Macours, 2010;Hou, 2010;Macours et al, 2012;Aker et al, 2016;N. D. Jensen et al, 2017;Asfaw et al, 2017;Knippenberg and Hoddinott, 2017;Adhvaryu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the months following the cyclone, both papers found that households that received the cash transfers recovered more quickly than those who did not, using a regression discontinuity design (Mansur et al, 2017;Ivaschenko et al, 2020). In the aftermath of a slow-onset climate shock (a drought), Del Carpio and Macours (2010) and Macours et al (2012) use a cluster randomised control trial to show that a bi-monthly conditional cash transfer implemented by the Nicaraguan government had positive persistent impacts on child health, development, and labour. In a different domain, a randomised control trial implemented in Sri Lanka several months after the 2004 tsunami found that a one-off cash grant to firms facilitated business recovery and investment (De Mel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%